Heart rate variability behavior in athletes after a sports concussion: A systematic review - Flores, Gonçalo (2023)
Objective: This systematic review aims to investigate the adaptations of the autonomic nervous system (ANS) after a concussion by measuring HRV in athletes over the age of 16 after injury. Methods: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Web of Science, Pubmed, SCOPUS, and Sport Discus were searched using predefined search terms to identify relevant original cross-sectional, longitudinal, and cohort epidemiological studies published before December 2021. Results: After screening 1737 potential articles, four studies met the inclusion criteria. Studies included participants with concussion (n = 63) and healthy control athletes (n = 140) who practised different sports. Two studies describe a decrease in HRV following a sports concussion, and one proposed that the resolution of symptoms does not necessarily reflect ANS recovery. Lastly, one study concluded that submaximal exercise induces alteration in ANS, not seen in rest after an injury. Conclusions: In the frequency domain, a decrease in high frequency power and an increase of low frequency/high frequency ratio is expected, as the activity of the sympathetic nervous system increases, and the parasympathetic nervous system decreases after injury. In the frequency domain, heart rate variability (HRV) may help monitor the activity of ANS evaluating signals of somatic tissue distress and early identification of other types of musculoskeletal injuries. Further research should investigate the relationship between HRV and other musculoskeletal injuries.